Simulation modeling and analysis of job release policies in scheduling an agile job shop with process sequence dependent setting time - Vinod, K.T.; Prabagaran, S.; Joseph, O.A. (International Journal of Engineering and Technology, 2017)
This paper analyses the effects of job release policies, priority scheduling rules and setup times on the performance of a dynamic job shop in a sequence dependent setup time environment. Two job release policies namely, immediate job release and job release based on a specified work-in-process are investigated. A simulation model of a realistic manufacturing system is developed for detailed analysis. The dynamic total work content method is adopted to assign the due dates of jobs. Six priority rules are applied for prioritizing jobs for processing on machines. Several performance criteria are considered for analyzing the system performance. The simulation results are used to conduct statistical tests. Analytical models have been formulated to represent the simulation model for post-simulation studies. These models are found to yield a satisfactory estimation of the system outputs.